JEJAK langkah Pak Harto / Team Dokumentasi Presiden RI; editor, G. Dwipayana, Nazaruddin Sjamsuddin - Dwipayana, G.; Nazaruddin Sjamsuddin; Team Dokumentasi Presiden RI (Citra Kharisma Bunda, 2003)
6 jilid : ilus. ; 21 cm.